Quality assessment in percutaneous coronary interventions: the QERMID Belgian PCI registry. Issue 4 (4th July 2018) - Hanet, Claude; Claeys, Marc J.; Carlier, Marc; Desmet, Walter
Abstract: Background : The recent increase in the number of interventional cathlabs that followed a moratorium of several years has resulted in an abrupt increase in the number of PCI and a dilution of the experience per centre and per operator. Methods: Based on data extracted from the national "Quality Oriented Electronic Registration of Medical Implant Devices" (QERMID) database, we compared the characteristics and outcome of patients treated in 2015 in the 21 newly (<3 years) approved PCI centres with those of patients treated in the 28 historical PCI centres. Results: The proportion of acute coronary syndromes was slightly higher in new than in historical centres (48% vs. 44%; p < 0.01) but few differences in co-morbidities were observed. Considering separately the patients treated for an acute coronary syndrome or for stable ischaemia, no significant difference in the overall in-hospital or 30-days mortality and in the proportion of same week bypass surgery was observed between newly approved and historical centres. In a substantial proportion (39%) of patients treated for stable angina or silent ischaemia, no test confirming the presence of ischaemia before PCI is reported, without significant difference between new and historical centres. Conclusions: Pending the limitations of the QERMID database, including a limited dataset and the absence of systematic on-site monitoring, no significant difference in the rate of major complications was identified between new and historical Belgian PCI centres.